2015
DOI: 10.1002/ajhb.22805
|View full text |Cite
|
Sign up to set email alerts
|

Does human ejaculate quality relate to phenotypic traits?

Abstract: A given man's phenotype embodies cues of his ancestral ability to effectively defend himself and his kin from harm, to survive adverse conditions, and to acquire status and mating opportunities. In this review, we explore the hypothesis that a man's phenotype also embodies cues to fertility or the probability that an ejaculate will fertilize ova. Female mate choice depends on the ability to discern the quality of a male reproductive partner through his phenotype, and male fertility may be among the traits that… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
9
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 142 publications
(162 reference statements)
0
9
0
Order By: Relevance
“…The origins of such strong male effects are unclear. It has been suggested that reproductive parameters may reveal variance in health and vigour, but this hypothesis is little supported in humans34 (apart from several infertility aetiologies35 or the damaging effects of cigarette smoking and other life-style factors36) or in species with secondary sexual traits that may serve as quality indicators37. The housing conditions that our stallions experience at the stud are expected to minimize variance in health and vigour, and we found no correlations between reproductive parameters and stallion age or size.…”
Section: Discussionmentioning
confidence: 99%
“…The origins of such strong male effects are unclear. It has been suggested that reproductive parameters may reveal variance in health and vigour, but this hypothesis is little supported in humans34 (apart from several infertility aetiologies35 or the damaging effects of cigarette smoking and other life-style factors36) or in species with secondary sexual traits that may serve as quality indicators37. The housing conditions that our stallions experience at the stud are expected to minimize variance in health and vigour, and we found no correlations between reproductive parameters and stallion age or size.…”
Section: Discussionmentioning
confidence: 99%
“…Oxidative stress also negatively impacts immune function and sperm quality by damaging immune and sperm cells [16,19]. Finally, the phenotype-linked fertility hypothesis proposes that male signals provide information about semen quality [20,21], which is an indicator of male reproductive health and fertility, as well as more general health [22,23].…”
Section: Introductionmentioning
confidence: 99%
“…Research on human ejaculate quality has focused on testing the phenotype-linked fertility hypothesis on the assumption that ancestral men pursuing short-term mating would have produced higher quality ejaculates more capable of fertilizing ova (Jeffery et al, 2016). Guided by a life history perspective, however, the current results suggest that ejaculate quality accords more strongly with parenting effort than with mating effort (Simmons et al, 2017).…”
Section: Discussionmentioning
confidence: 99%
“…The results of the current study are preliminary. Additional research is needed to identify which phenotypic traits of men are reliably associated with ejaculate quality (see Jeffery et al, 2016, for an extended discussion) and to confirm whether ejaculate quality is reliably associated with other measures and indicators of life history strategies. Measurement of within-human variation of life history strategy has been the subject of debate since the data reported here were collected (Richardson et al, 2017).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation